2001
DOI: 10.1111/j.1574-6941.2001.tb00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced degradation of phenoxyacetic acid in soil by horizontal transfer of the tfdA gene encoding a 2,4-dichlorophenoxyacetic acid dioxygenase

Abstract: Few studies have investigated the possible impact of in situ gene transfer on the degradation of xenobiotic compounds in natural environments. In this work we showed that horizontal transfer of the tfdA gene, carried on plasmid pRO103, to phenol degrading recipient strains significantly increased the degradation rate of phenoxyacetic acid in sterile and non-sterile soil microcosms. The tfdA gene encodes a 2,4-dichlorophenoxyacetic acid/2-oxoglutarate dioxygenase and by complementation with the phenol degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…To date, previous retrospective studies have had limited application to the study of LGT as a process that shapes the genetic diversity of natural communities. Rather, this issue has been addressed either by demonstrating transfer in microcosms (4,15) or by examining the potential for…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, previous retrospective studies have had limited application to the study of LGT as a process that shapes the genetic diversity of natural communities. Rather, this issue has been addressed either by demonstrating transfer in microcosms (4,15) or by examining the potential for…”
Section: Discussionmentioning
confidence: 99%
“…The time scale for the acquisition of new genetic material by LGT, estimated to occur at a rate of 31 kb per 10 6 years in E. coli (32), may mean that microcosm studies have little relevance. Indeed, in many cases, LGT could be detected only following nutrient amendment (15), by inoculation of unrealistically high numbers of donor and recipient strains (4), or in the presence of selection for phenotypes encoded by the transferred genes (81). Observing LGT in microcosm studies simulating deep subsurface environments may be particularly difficult, as low population densities and metabolic rates may require prohibitively long incubation times before transformants and transconjugants are obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this bacterium could be naturally transformed therein by artificially added or indigenous transgenic DNA (10,11). Yet, other plant compartments could be as propitious to HGT; for example, the residuesphere (i.e., the naturally degrading plant material at the interface with soil) has been shown to provide conditions for growth and conjugal gene transfer between indigenous soil bacteria (7,34). The litter and the residues of annual crops represent an important amount of final plant production, which are often left in the field after harvest and, in most cases, account for up to 60% of the world's plant biomass (14).…”
mentioning
confidence: 99%
“…The application of P. putida ZWL73 in contaminated soil with 4-chloronitoben-zene (4CNB) was investigated by Niu et al (32). In another research, it was found that tfdA gene located in plasmid pRO103 in phenol-degrading recipient strains leads to significantly biodegradation rate of phenoxy acetic acid in sterile and non-sterile soils (33). In the present study, the pUC18-nahH recombinant vector was generated and transferred into P. putida and degradation of oil in polluted soil was increased statistically via evaluation of phenanthrene and pyrene as an indicator.…”
Section: Discussionmentioning
confidence: 99%